Determinant of Early Breastfeeding Initiation Program Execution by Midwives in Public Health Centers – Magelang District - Tulus Puji Hastuti; Mundarti Mundarti; Sri Widatiningsih (Jurnal Riset Kesehatan, 2012)
The purpose of this study was to identify determinant factors related to the execution of early breast feeding initiation by midwives in the district of Magelang. The study was observational research with crosssectional approach. Respondents were 65 public health center midwives. Sampling method for choosing the public health centers was stratified random sampling, then midwives who had been certified for Normal Birth Care plus Early Breastfeeding Initiation were taken. Majority of the respondents had short working period. There was a relation between working period and the execution of early breasfeeding initiation with p = 0,046 and r = - 0,248. There was no relationship between age, knowledge, and motivation with execution of early breastfeeding initiation program.